Respostas
respondido por:
4
1/23 + 23/2 = x - 6/23 isolando o x
x = 1/23 + 23/2 +6/23 tirando mmc
x = (2.1)+(23.2)+(2.6) / 46
x = 2+46+12 / 46
x= 60 / 12
x = 5
x = 1/23 + 23/2 +6/23 tirando mmc
x = (2.1)+(23.2)+(2.6) / 46
x = 2+46+12 / 46
x= 60 / 12
x = 5
respondido por:
0
Resposta:
1/23 + 23/2 = x - 6/23 isolando o x
x = 1/23 + 23/2 +6/23 tirando mmc
x = (2.1)+(23.2)+(2.6) / 46
x = 2+46+12 / 46
x= 60 / 12
x = 5
Explicação passo-a-passo:
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás